Strategi Farmako-invasif pada STEMI Akut - Isman Firdaus (Jurnal Kardiologi Indonesia, 2011)
Recently, primary percutaneous coronary intervention (PCI) is the best option for reperfusion in STEMI patients, in clinical trials has lower rates of reinfarction, stroke and mortality than fibrinolytic therapy. Because of system delays in routine practice, prehospital administration of fibrinolytic therapy may lead to similar clinical outcomes, especially in those patients who present in early onset after symptom. Assessment of failed reperfu-sion for rescue PCI and invasive strategy after fibrinolitic therapy leading similar outcome with primary PCI. This review focuses on the timing of, and indications for, an invasive strategy after fibrinolytic therapy, including that for failed pharmacological reperfusion.